Perspektywy współpracy Polski z Ukrainą - Butyter, Daniel (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
This article presents the dynamics of development of the Ukrainian-Polish bilateral relations from the beginning of the 1990s to the beginning of the 21st century and defines their political component, formulates the role of Poland in the foreign policy of Ukraine, analyzes the impact of enlargement processes of NATO and the EU on the dynamics and prospects of the dialogue between Ukraine and Poland. The author tries to explain the significance of the Ukrainian-Polish relations for the support of regional and European security and to investigate the influence of leading states of the West and Russia on the development of Ukrainian-Polish relations and to define their role and importance. Special attention is paid to therole of Poland in resolving the political and economic crisis in Ukraine, which began in November 2013, after the refusal of government of ex-President of Ukraine Viktor Yanukovych to sign the Association Agreement with the EU. Thus the paper is the prediction trends and prospects for further development of cooperation between Kyiv and Warsaw.
Keywords: Polska; Ukraina; umowa stowarzyszeniowa; współpraca transgraniczna